- PENILAIAN BAHAYA DAN RENCANA PENGENDALIAN RISIKO BAGI PENGUNJUNG DI PUNCAK LALANA, CIAMPEA, BOGOR: - - Febriani, Andini; Hasibuan, Ratna; meiganati, kustin bintani (Jurnal Nusa Sylva, 2024)
Cibadak Karst Area which is located in Ciampea District has a high selling value so it can be utilized by the tourism sector, especially ecotourism. The Cibadak Karst Area is in the work area of Perum Perhutani, Bogor Forest Management Unit (KPH), Jawa Barat and Banten Regional Division. Currently the Lalana Peak ecotourism area is managed by the surrounding community. Lalana Peak is one of the main destinations for visitors who travel to the Cibadak Karst Area because it has a slightly spurring hiking trail adrenaline and has a unique exokarst landscape. The instrument used in this research is HIRARDC (Hazard Identification Assesment and Risk Assesment and Determining Control) form and this research is using analysis guidelines guided by the Australian Standard/ New Zealand Standard for Risk Management (AS/NZS 4360:2004). The interpretation track of Lalana peak has the hazard potential consist of physical, biological and human activity hazards. Risk level identification of potential hazard in the interpretation track of Lalana Peak are acceptable, priority 3, substantial and priority 1. The Risk control plan that can be carried out by the manager Lalana Peak area are technical, substitution and administration control.